2021
DOI: 10.3389/fmed.2021.673500
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors of Postpartum Hemorrhage in China: A Multicenter Retrospective Study

Abstract: Background: Postpartum hemorrhage (PPH) is a leading cause of maternal morbidity and mortality worldwide but the incidence and its risk factors in China is limited. The objective of this study is to investigate the incidence and the risk factors of PPH in Chinese women.Methods: A multi-center retrospective study of pregnant women at ≥28 weeks of gestation was conducted. Logistic regression was used to identify potential risk factors of PPH and receiver operating characteristic curve was used to evaluate the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 50 publications
4
18
0
1
Order By: Relevance
“…The incidence of PPH (26.5%) in our cohort was much higher than that in the general female population in China (.81%), consistent with that in previous international studies 25–27 . Several guidelines suggested that antifibrinolytic drugs or coagulation factors could be applied to prevent PPH 28–30 .…”
Section: Discussionsupporting
confidence: 89%
“…The incidence of PPH (26.5%) in our cohort was much higher than that in the general female population in China (.81%), consistent with that in previous international studies 25–27 . Several guidelines suggested that antifibrinolytic drugs or coagulation factors could be applied to prevent PPH 28–30 .…”
Section: Discussionsupporting
confidence: 89%
“…Of the 1500 women included in our study, we obtained an incidence of PPH of 28%, higher than previous studies [ 8 , [37] , [38] , [39] ], which range from 0.5% to 16%, although it is closer to that found in an Italian study [ 28 ] that reports 24%. It may be possible due to a thorough strategy for quantifying the bleed and for recording the data, taking into account that an objective measurement of bleeding is performed, which makes us think that in reality we may miss many cases of PPH when performing a subjective or visual estimation of bleeding because it could be imprecise.…”
Section: Discussionsupporting
confidence: 47%
“…For example, both the study from the Southern Ethiopia and Mali showed that antepartum anemia mothers are more likely to suffer from PPH 32,33 . The effect of placenta previa has also been reported in many studies 15,34,35 . A study from China found the patients with complete placenta previa had higher risk of PPH than those incomplete or no placenta previa 34 .…”
Section: Variablesmentioning
confidence: 60%
“…A study from China found the patients with complete placenta previa had higher risk of PPH than those incomplete or no placenta previa 34 . Therefore, the guidelines 36 usually recommend planned cesarean delivery for better maternal outcomes 35 . Placenta accreta refers to the penetration of placental villi into part of the muscular layer of the uterine wall.…”
Section: Discussionmentioning
confidence: 99%